Global Environment Outlook - GEO-6: Technical Summary - Environment, UN (Physical Sciences, 2021)
This Technical Summary synthesizes the science and data in the GEO-6 report, making it accessible to a broad audience of policymakers and scientists. It highlights the need for urgent action and identifies transformational pathways towards environmental and economic recovery in a post-COVID-19 era. Also available as Open Access on Cambridge Core.